2021
DOI: 10.3389/fped.2020.623689
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring and Outcome of Infliximab Therapy in Pediatric Onset Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) with pediatric onset has become more prevalent during past decades. Thus, the number of patients with moderate to severe disease subtype treated with antagonists to tumor necrosis factor alpha (TNFα) has concurrently risen. Most pediatric patients initially respond to these drugs but will need dose escalation during the first year of therapy. As pediatric data regarding therapeutic drug monitoring during therapy with TNFα-blocker adalimumab are sparse, this review focuses on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…Multiple prospective studies on the exposure-outcome relationship in both adult and paediatric IBD and post-hoc analyses of RCTs have shown a positive correlation between drug concentrations and favourable therapeutic outcomes (table 1). 102,103 Studies observed similar results during induction and maintenance therapy. In the large prospective PANTS study, 28 infliximab trough concentrations of at least 7•0 μg/mL and adalimumab concentrations (at or close to trough concentration) of at least 12•0 μg/mL at week 14 were associated with clinical remission at both week 14 and week 54.…”
Section: Prospective Studies and Post-hoc Analyses Of Rctsmentioning
confidence: 64%
“…Multiple prospective studies on the exposure-outcome relationship in both adult and paediatric IBD and post-hoc analyses of RCTs have shown a positive correlation between drug concentrations and favourable therapeutic outcomes (table 1). 102,103 Studies observed similar results during induction and maintenance therapy. In the large prospective PANTS study, 28 infliximab trough concentrations of at least 7•0 μg/mL and adalimumab concentrations (at or close to trough concentration) of at least 12•0 μg/mL at week 14 were associated with clinical remission at both week 14 and week 54.…”
Section: Prospective Studies and Post-hoc Analyses Of Rctsmentioning
confidence: 64%
“…Given its crucial role in the inflammatory process, this molecule has been the therapeutic target of specific pharmacological treatments, the most significant example of which is infliximab, the use of which is approved for pathologies such as rheumatoid arthritis and chronic inflammatory bowel diseases (Crohn’s disease and ulcerative colitis) [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decisions on management were made at the discretion of the treating physician and were based on the routine use of the clinical symptom index [17], fecal calprotectin [18][19][20], blood inflammatory marker and drug level measurements, and the presence of drug antibodies when appropriate [7,16]. Clinical disease activity was retrospective scored according to Physician Global Assessment (PGA) on a scale of 1-3 [21].…”
Section: Methodsmentioning
confidence: 99%
“…Most patients with PIBD initially respond to anti-TNFa therapy but will need dose escalation during the first year of therapy [12][13][14][15]. To guide therapeutic decisions, the use of trough level measurements of infliximab has been established [9,16]. In PIBD, however, published reports on adalimumab levels are scarce.…”
Section: Introductionmentioning
confidence: 99%